The Impact of Service Transformation, Self-Check-in on Pelita Air Loyalty, Mediated by Customer Satisfaction - Assyfa Putri Damongayo; Kurotul Aeni Habibatul Hamdiah; Alit Sodikin; Yuwono D. Sucipto (Jurnal Ilmu Multidisiplin, 2025)
This study examines the effect of implementing self-check-in machines on customer satisfaction as part of Pelita Air’s service transformation at Soekarno-Hatta International Airport in 2024. This study uses a quantitative method by distributing questionnaires to Pelita Air passengers who use self-check-in machines with a purposive sampling technique. From a population of 505.022 passengers, a sample of 100 respondents was taken. Data analysis used SEM-PLS (Structural Equation Model-Partial Least Square) with independent variables of service transformation (X1) and Implementation of self-check-in machines (X2), Customer Satisfaction (Y) as a mediating variable and Customer Loyalty (Z) as a dependent variable. The result of this study are that service transformation and implementation of self-check-in machines have a significant direct effect on customer loyalty mediated by customer satisfaction.